Car maintenance manual based on augmented reality (CAMAR) / Abdul Muiz Mustaffa - Mustaffa, Abdul Muiz (2019)
Car maintenance is a crucial aspect for an automotive user as it will help to extend the lifespan of the vehicle occasionally. Besides, the use of user manual for vehicle maintenance is no longer relevant because it only limits the amount of user interactions occurs, hard to navigate, and usually printed in black and white to save cost. Therefore, this project is intended to use Augmented Reality (AR) as the cutting edge technology in developing an interactive car maintenance mobile learning. The interactive learning environment is an approach to help the users become more engaged and retain more information compared to the traditional approach, in this case, the user manual. The objectives of this project are to identify the user requirements of CaMAR AR application in enhancing user experiences and interactions mainly, to design, and to develop CaMAR AR mobile application by following the Rapid Application Development (RAD) methodology throughout the development process. Markerless detection technology that contain various advance object tracking methods becomes one of the motivations in developing this project while fulfilling the solution to the problems. This project will benefit numerous parties especially regular car users in maintaining their vehicle and the automotive industry as the added value to their product. In conclusion, CaMAR AR application may assist the car users in conducting car maintenance while enhancing the user experience through virtual environment.